Entre tradition et transgression, - Arlette Bouloumié (Carnets)
We want to study, in Michel Tournier’s works, the rewriting of popular tales of the oral tradition (Perrault) and those inspired by German romanticism, or by the Bible or One Thousand and one nights. We shall give Tournier’s definition of the tale in opposition with the novel and his analogy with the myth.The characteristics of the rewriting: inversion, actualization, disturbing quaintness or comic, poetry or realism, use of reminiscences, double reading, nature of fantastic, will be studied.In each text, the presence, full of humour, of the teller, shows the importance for Tournier of the oral tradition and of the philosophical message.The texts studied are, in Le Coq de Bruyère: “La Fugue du Petit Poucet”, “Tristan Vox”, “La famille Adam”, and in Le Médianoche amoureux: “La légende de la peinture” and “Les deux banquets ou la commémoration”.